A Story of Developing the Idea of Plasma-Sheet Flow Braking - Shiokawa, Kazuo (Frontiers in Astronomy and Space Sciences, 2022)
This paper reports a story of developing the idea of Earthward ion flow braking in the near-Earth plasma sheet and its relationship with substorm onset processes. This idea and the data that supports it is the basis for today’s two competing models for substorms: the near-Earth neutral-line model and the current disruption model. The idea came up when the author was staying in the Max Planck Institute for Extraterrestrial Physics (MPE) from July 1996 to June 1997. The story addresses the colleagues and mentors who had contributed to the development of this idea. The lessons learned from this story are also summarized for students and early-career scientists for their development of new scientific ideas.